Looking for strong leaders? – How uncertainty affects leadership preferences - Malassu, Kaisa (2024)
The environment we operate in has changed quite radically in a relatively short time frame. The level of uncertainty has increased and the crises we face both in our societies and within organisations have changed their shape and form, from being isolated incidents to being transboundary by nature and part of global turbulences and movements. The purpose of this study is to explore the concept of uncertainty in the general environment, and how it affects what is expected from leaders. The theoretical background drawn from earlier crisis leadership research and the uncertainty-identity theory (e.g., Hogg, 2007) suggest that uncertainty leads people to heavily rely on their leader (Hogg & Rast, 2016; Rast et al., 2012) and people tend to start preferring strong and directive forms of leadership – even to the extent of preferring autocratic leadership over more democratic forms of leadership (Rast et al., 2013). Based on the theoretical findings, this study hypothesises that uncertainty has a positive relationship with preference of strong leadership. The type or cause of uncertainty should play no role, and the relationship does not disappear when controlled with social group memberships. The data analysed in this study (n= 2,045) is collected for the Finnish Business and Policy Forum (EVA) by Taloustutkimus during fall 2023 as a part of a survey series EVA Surveys on Finnish Values and Attitudes. The data is analysed with statistical analysis methods. Different types of uncertainty are defined through explorative factor analysis. The main relationship between uncertainty and preference of strong leadership is then tested with multiple linear regression (MLR). The results of the study suggest that financial uncertainty and uncertainty related to one’s physical integrity, i.e., uncertainty from threat of violence, increase the preference of strong leadership. The perceived salience and importance of the cause of uncertainty (Hogg, 2007), and the uncertainty’s relation to one’s self-concept (Rast, 2015) seemed to affect the low impact of uncertainty from hybrid threats to preference of strong leadership. Further studies on the effects of uncertainty from opinionated and polarised threats and gender are required. Future research directions are suggested.